Quantitative Study of Factors Associated with Breast Cancer among Women Reporting to a Tertiary Care Hospital in Karnataka - Venkatesh Gonibeedu; Vamsi Kakileti (Medsci Publications, 2020)
Introduction: Numerous epidemiological studies performed throughout the world have confirmed the role of many risk factors. However, evidence suggests that international variation in the burden of breast cancer reflects differences in the patterns of risk factors. Hence this study is undertaken to assess the risk factors associate with breast cancer in a district in Karnataka. Method: This is a Case control study to assess the risk factors associated with breast cancer among cases attending radiation unit of Hassan institute of medical sciences during 2019. Results: There was a significant association of breast cancer with menarche attained at or less than age 13 years (OR=2.43, CI: 1.09-5.4, p<0.029), usage of oral contraceptive (OR=2.04: CI 1.61-2.42; p<0.1), and menopause attained before age 50 (OR=5.2: CI2.2-12.2; p<0.00). Our study also found that for every year increase in age for 1st birth, controls not being diseased decreased by 26% was statistically significant (OR=0.76; CI:0.61-0.89; p<0.002) and for every parity added, controls not being deceased increased by 1.13 time (OR=1.13; CI:0.69-1.8;p<0.6). Conclusion: District cancer control programme should advice women, to consume non-vegetarian food in moderation, promote physical activity form early age to maintain ideal body mass index.